GW24-e1000 Danhong injection combined with Adipose tissue-derived stem cells transplantation promotes angiogenesis after hind limb ischaemia in diabetic nude mice through a endogenous hydrogen sulfide dependent mechanism. (1st October 2013) - Feng, Wu; Zhiqing, He; Ruizhen, Ji; Xin, Wang; Zonggui, Wu; Chun, Liang
Abstract : Objectives: To investigate the efficacy of Danhong injection (DH) combined with Adipose tissue-derived stem cells (ADSCs) transplantation on angiogenesis in diabetic hind limb ischaemia model and the related molecular mechanism. Methods: Male nude mice were induced to diabetes by injection of streptozontocin intraperitoneal. Diabetes modelling success was identified by random blood glucose levels higher than 16 mmol/L twice. After 2 weeks, hind limb ischaemia model was established by ligation and excision of femoral artery. Forty 8-week-old nude mice were randomly divided into four groups: group I (n = 10): diabetic hind limb ischaemia model, group II (n = 10): ADSCs (1 × 10 6 cells, i.m.) transplantation, group III (n = 10): DH (2 μL/g × 7 days) i.p., group IV (n = 10): combination of DH and ADSCs transplantation. After 2 weeks, perfusions, vessel regeneration, and local VEGF expression of lower limbs among different groups were evaluated with LDPI, X-ray arterography, real-time PCR and ELISA respectively. And microvascular densities of lower limb muscle were investigated using immunocytochemical staining of CD31. The expression of cystathionine beta synthase (CBS), cystathionine gamma lyase (CSE), 3-mercaptopyruvate sulfur transferase (3-MST), which are three major sources for endogenous enzymatic production of hydrogen sulfide (H2 S), were measured by western blot. Hydrogen sulfide tissue concentration in mice ischaemic muscles was measured by pre-column derivatisation with monobromobimane (mBrB) and the corresponding reversed-phase high performance liquid chromatography (RP-HPLC)-fluorescence quantitation method. Results: Only ADSCs transplantation or DH ip could significantly increase perfusion, promote the formation of collateral circulation, and enhance local VEGF, CBS/CES/3-MST and H2 S expression after 2-week intervention compared with control group, without decreasing blood glucose and increasing serum H2 S and VEGF. And meanwhile capillary density of the ischaemic hind limb showed similar trend by CD31 staining. While combination of DH and ADSCs transplantation could increase the protective effects further vs DH ip or ADSCs transplantation alone. Conclusions: ADSCs transplantation or DH ip alone could improve ischaemia perfusion and vascular tube-like generation in diabetic hind limb models through endogenous hydrogen sulfide actions. And, combination of DH ip and ADSCs transplantation could exert more protective effects. which might be a novel therapy strategy against diabetic hind limb ischaemia.